2009
DOI: 10.1038/mt.2009.1
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Lentiviral Vector Design Improves Titer and Transgene Expression of Vectors Containing the Chicken β-Globin Locus HS4 Insulator Element

Abstract: Hematopoietic cell gene therapy using retroviral vectors has achieved success in clinical trials. However, safety issues regarding vector insertional mutagenesis have emerged. In two different trials, vector insertion resulted in the transcriptional activation of proto-oncogenes. One strategy for potentially diminishing vector insertional mutagenesis is through the use of self-inactivating lentiviral vectors containing the 1.2-kb insulator element derived from the chicken beta-globin locus. However, use of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 40 publications
3
72
0
2
Order By: Relevance
“…This insulator was originally described as a barrier insulator but may have blocking activity as well when repeated in tandem. 34,37,38 Similar to previously developed insulated retroviral vectors, 53,54 the insulators were positioned in the U3 region of the 3¢ LTR of replicationincompetent FV vectors (Fig. 1b).…”
Section: Development Of Insulated Fv Vectorsmentioning
confidence: 88%
“…This insulator was originally described as a barrier insulator but may have blocking activity as well when repeated in tandem. 34,37,38 Similar to previously developed insulated retroviral vectors, 53,54 the insulators were positioned in the U3 region of the 3¢ LTR of replicationincompetent FV vectors (Fig. 1b).…”
Section: Development Of Insulated Fv Vectorsmentioning
confidence: 88%
“…When genetically modified stem cell transplantation becomes a possible option for treating β-thalassemia, the co-existence of repaired cells with those still expressing the genetic defect will be an expected scenario, not in an allogeneic environment, but in an autologous one. 27,[31][32][33][34][35][36] Also in this light, a better understanding of the mechanisms underlying the establishment of quantitatively different red cell/nucleated cell chimerism will be particular relevant. …”
Section: Discussionmentioning
confidence: 99%
“…On the basis of these data, the 5-fold higher titer of vector V5m3-400 implies that the size of cHS4, incorporated in the U3 region, is probably a critical parameter in defining the titer of the vector, because GGHI combines a large insulator and a relatively small expression cassette (1.7 kb), whereas V5m3-400 combines a small core insulator (400 bp) and a large expression cassette. The majority of globin vectors used in the globin gene therapy field do not contain insulators (Imren et al, 2002;Rivella et al, 2003;Hanawa et al, 2004;Lisowski and Sadelain, 2007;Miccio et al, 2008), although the use of the latter is considered almost necessary because not only do they increase expression of b-globin (Arumugam et al, 2007) but they also have been proven in a large number of studies (Desprat and Bouhassira, 2009;Hanawa et al, 2009) to act more efficiently in reducing the risk of insertional mutagenesis. In addition, Arumugam and colleagues (2009) showed that the core sequence of cHS4 alone does not insulate viral vectors effectively and that both 3¢ as well as 5¢ sequences are needed for full insulator activity.…”
Section: Discussionmentioning
confidence: 99%